2014
DOI: 10.1101/cshperspect.a015263
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Epidermal Differentiation

Abstract: In a cell, the chromatin state is controlled by the highly regulated interplay of epigenetic mechanisms ranging from DNA methylation and incorporation of different histone variants to posttranslational modification of histones and ATP-dependent chromatin remodeling. These changes alter the structure of the chromatin to either facilitate or restrict the access of transcription machinery to DNA. These epigenetic modifications function to exquisitely orchestrate the expression of different genes, and together con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 123 publications
(144 reference statements)
0
65
0
1
Order By: Relevance
“…Understanding how this complex functions in stem cells in vivo is of paramount importance, as a wide variety of human genomic studies have revealed the importance of the Polycomb proteins for different human diseases (Perdigoto et al , 2014b; Sauvageau and Sauvageau, 2010). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding how this complex functions in stem cells in vivo is of paramount importance, as a wide variety of human genomic studies have revealed the importance of the Polycomb proteins for different human diseases (Perdigoto et al , 2014b; Sauvageau and Sauvageau, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Polycomb repressive complex (PRC) 2 is a major chromatin repressor (Schwartz and Pirrotta, 2013) that regulates tissue development and fate control, and is implicated in a number of diseases, including cancer (Margueron and Reinberg, 2011; Perdigoto et al , 2014b; Sauvageau and Sauvageau, 2010; Schwartz and Pirrotta, 2008; Surface et al , 2010). PRC2 consists of the core subunits EED, Suz12, and the histone methyltransferases Ezh1 or Ezh2, which catalyse the tri-methylation of lysine 27 of histone H3 (H3K27me3), resulting in gene silencing by chromatin compaction (Margueron et al , 2008; Schwartz and Pirrotta, 2013; Simon and Kingston, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Cell differentiation is an insightful example of the importance of epigenetic regulation [1]. An example of epigenetic regulation is a fertilized egg that gives rise to an organism that consists of hundreds of different cell types, morphologically and functionally, while preserving genetic information contributed by both parents [2, 3].…”
Section: Introductionbmentioning
confidence: 99%
“…Epigenetic regulators exhibit both activating and repressive effects on chromatin in keratinocytes (KCs): histone demethylase Jmjd3, ATP-dependent chromatin remodeler Brg1, and genome organizer Satb1 promote terminal KC differentiation, while DNA methyltransferase DNMT1, histone deacetylases HDAC1/2, and Polycomp components Bmi1 and Ezh1/2 stimulate proliferation of progenitor cells via repression of the genes encoding cell cycle inhibitors, as well as inhibit premature activation of terminal differentiation-associated genes (reviewed in (Eckert et al, 2011;Frye and Benitah, 2012;Botchkarev et al, 2012;Perdigoto et al, 2014).…”
mentioning
confidence: 96%
“…The program of epidermal development and keratinocyte differentiation is governed by coordinated involvement of several transcription factors (p63, AP-1, Klf4, Arnt, and so on), signaling pathways (Wnt, Bmp, Hedgehog, EGF, Notch, FGF, and so on), and epigenetic regulators (DNA/histonemodifying enzymes, Polycomb genes, higher-order and ATP-dependent chromatin remodelers, and non-coding RNAs) that control expression of lineage-specific genes (reviewed in (Frye and Benitah, 2012;Botchkarev et al, 2012;Perdigoto et al, 2014)). …”
mentioning
confidence: 98%